Supervised Machine Learning in SAS Viya: Development of a Supervised Machine Learning pipeline in SAS Viya for comparison with a pipeline developed in Python - Neves, Guilherme Luís Ataíde (2023)
Internship Report presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Business Analytics